Does foreign direct investment contribute to unemployment in home countries? An empirical survey - Jamuna Prasad Agarwal (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
According to investors' motivations, outward foreign direct investment (FDI) can be distinguished between natural resources seeking, market seeking or efficiency seeking. In the first two types, unemployment resulting from export substitution and reimports is expected to be considerably less than employment emanating from additional exports of capital equipment, intermediate goods and new product lines to foreign affiliates, and the need for more office jobs in the home countries. The efficiency seeking FDI may cause more unemployment due to export substitution and reimports than employment through additional exports to host countries. Since the first tivo types constitute generally the bulk of FDI. net employment effect on home countries should ceteris paribus be positive.
Keywords: 330; Direktinvestition; Arbeitsnachfrage; Arbeitsmarkt; Standortwettbewerb; Industriestaaten